Radioembolization for Cholangiocarcinoma - Ali, Aamir; Manzoor, Komal; Weinstein, Jeffrey L.; Faintuch, Salomao; Ahmed, Muneeb; Sarwar, Ammar (Digestive Disease Interventions, 2021)
Cholangiocarcinoma is the second most common primary hepatic malignancy which accounts for 13% of total cancer mortality worldwide. Surgical resection is the only curative treatment for localized disease; however, the majority of patients present when the tumor is unresectable. The incidence of the intrahepatic subtype of cholangiocarcinoma is increasing worldwide. Current standard of care in patients with unresectable intrahepatic cholangiocarcinoma is systemic chemotherapy; however, yttrium-90 transarterial radioembolization (Y90-TARE) is under investigation for the treatment of intrahepatic cholangiocarcinoma with promising trials and published clinical experience. This review critically evaluates the role of Y90-TARE in the management of intrahepatic cholangiocarcinoma.
Keywords: cholangiocarcinoma; yttrium-90; radioembolization